1995
DOI: 10.1017/s0252921100036770
|View full text |Cite
|
Sign up to set email alerts
|

Mode Identification of the β Cephei star BW Vulpeculae

Abstract: Abstract. We identify the pulsation mode of BW Vul by means of both the moment method and the method of photometric amplitudes and find a radial pulsation. We briefly study the non-linear behaviour of BW Vul.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…Nota bene, both calculations provide the same values for T eff and log g and they agree very well with previously determined values (e.g. T eff = 23 227 K by Aerts et al 1995). …”
Section: Synthetic Spectrum For Bw Vulsupporting
confidence: 88%
See 2 more Smart Citations
“…Nota bene, both calculations provide the same values for T eff and log g and they agree very well with previously determined values (e.g. T eff = 23 227 K by Aerts et al 1995). …”
Section: Synthetic Spectrum For Bw Vulsupporting
confidence: 88%
“…It is unlikely that line doubling in BW Vul is caused by non-radial modes as Aerts et al (1995) demonstrated that this star pulsates in a radial mode. Therefore, it is far more likely that the line doubling originates from shock waves as described by Mathias et al (1998).…”
Section: Line Doublingmentioning
confidence: 94%
See 1 more Smart Citation
“…This is justified because the amplitude of the harmonic is about 4 times lower than the one of f 1 . This type of approach turned out to be valid for the β Cep star BW Vul, for which the relative contribution of the first harmonic to the radial-velocity variation is also a factor near 1/4 of the one of the frequency itself (Aerts et al 1995). The results of the MM are given in Table 3.…”
Section: Multiperiodic Oscillationsmentioning
confidence: 99%
“…As already indicated by the photometry, the dominant mode does not behave sinusoidally at all and v 1 has a peak-to-peak amplitude of about 90 km s −1 . This makes HD 180 642 the β Cephei star with the third largest peak-to-peak radial-velocity amplitude, BW Vul having ∼180 km s −1 (Crowe & Gillet 1989;Aerts et al 1995;Mathias et al 1998) and σ Sco having ∼110 km s −1 (Mathias et al 1991). More unusual is the presence of a so-called stillstand, i.e., a plateau at half the descending branch of the radial velocity curve.…”
Section: Frequency Analysismentioning
confidence: 99%